Computer Vision Based on Computational Intelligence and Its Application Analysis. Issue 4 (October 2020) - Huang, Feiyu
Abstract: Under the background of modern information technology intelligence, the comprehensive processing technology formed by the processing and calculation of information and data. The purpose of this paper is to analyze the vision application under the intelligent computer, and the computer and technology application based on intelligent integration is to scientifically design various computer sectors by expanding and extending the functions of the computer. The method used in this paper is based on face recognition in computer vision. First, image recognition is used as the image description, and then the feature points are used to extract the K-means clustering algorithm. The clustering algorithm is used to determine the k value of M., Then clustering can get M keywords, generate a classification model using the independent features of the histogram, and then use local and global visual features to extract computer vision recognition data with obstacles. Experimental research results show that computer vision is an important development direction of artificial intelligence, which uses cameras and computers instead of human eyes to perceive, recognize, track and measure targets, obtain three-dimensional information of corresponding scenes, and process captured pictures or videos.